Disease spectrum of alcoholic liver disease in Beijing 302 Hospital from 2002 to 2013: A large tertiary referral hospital experience from 7422 patients. Issue 7 (February 2017) - Huang, Ang; Chang, Binxia; Sun, Yin; Lin, Huiming; Li, Baosen; Teng, Guangju; Zou, Zheng-Sheng
Abstract : Abstract: Alcohol consumption in China has substantially increased over the last 3 decades and the number of patients with alcoholic liver disease (ALD) is rising at an alarming rate. However, accurate and representative data on time trends in its hospitalization rates are not available. The aim of this study is to assess the current status and burden of ALD in China by analyzing the data from a large tertiary referral hospital, Beijing 302 Hospital. Data were retrospectively recorded from patients diagnosed as ALD in Beijing 302 Hospital from 2002 to 2013. The disease spectrum and biochemical parameters of each patient were collected. The patients with ALD accounted for 3.93% (7422) of all patients (188, 902) with liver diseases between 2002 and 2013. The number of patients hospitalized with ALD increased from 110 in 2002 to 1672 in 2013. The ratio of patients hospitalized with ALD to all patients hospitalized with liver diseases was rising almost continuously and increased from 1.68% in 2002 to 4.59% in 2013. Most patients with ALD were male. Age distribution of ALD hospitalization showed that the highest rate was in 40- to 49-year-old group in subjects. Notably, the annual proportion of severe alcoholic hepatitis (SAH) increased 2.43 times from 2002 to 2013. We found the highest levels of mean corpuscular volume, the aspartate aminotransferase/alanine aminotransferase ratio, total bilirubin, international normalized ratio, and alkaline phosphatase in SAH patients, while serum levels of hemoglobin, albumin, and cholinesterase were significantly decreased in SAH group. Among these ALD, the SAH patient population has the worst prognosis. Alcoholic cirrhosis (ALC) is the most common ALD, and annual admissions for ALC increased significantly during the analyzed period. The number of hospitalized patients with ALD and the annual hospitalization rate of ALD were increasing continuously in Beijing 302 Hospital from 2002 to 2013. More attention should be paid to develop population-based effective strategy to control ALD.